EMUs Electrical Connector Life Prediction Based on Accelerated Degradation Data - Jie MA; Lide WANG; Chuan YUE; Ping SHEN; Ji QIU (机车电传动)
The electrical connectors of EMUs play a very important role in train operation. In order to improve the efficiency and accuracy of life prediction of electrial connector products, the connector accelerated test was designed and implemented, and the product performance degradation data was obtained. Using physical model of life prediction and data processing algorithm and accelerated degradation data modeling process based on degradation distribution, the reliability and life evaluation of EMUs electrical connectors were realized. The life prediction software was also designed and implemented, which realized degraded data preprocessing, data distribution fitting, model parameter calculation, model curve rendering and life value prediction.